Application of Augmented Reality for Introduction Of The Unit Ted (Technical Record & Configuration Management) Structure In PT. GMF Aeroasia.Tbk Based On Android: Application of Augmented Reality for Introduction Of The Unit Ted (Technical Record & Configuration Management) Structure In PT. GMF Aeroasia.Tbk Based On Android - Anggun Wibowo; Iskandar Fitri; Deny Hidayatullah (Institute of Computer Science (IOCS), 2020)
The utilization of augmented reality technology is now more widespread. At present many companies have used the technology to introduce the company and its products to the public. Augmented reality is a picture of a real virtual object in 3D. Augmented reality can be applied to an android smartphone. Here i will make an application to introduce the organizational structure of the TE (Technical Engineering) service especially in the TED (Technical Record & Configuration Management) unit which is divided into 5 sub units within the PT.GMF (Garuda Maintenance Facility) AeroAsia Tbk. the company where I work. In making this Augmented Reality based application, i used Unity and Vuforia. Which later this application will be compiled into an “apk” file that can be installed on our android smartphone.